2018
DOI: 10.2196/resprot.7349
|View full text |Cite
|
Sign up to set email alerts
|

Possible Risk Factors for Severe Anemia in Hospitalized Sickle Cell Patients at Muhimbili National Hospital, Tanzania: Protocol for a Cross-Sectional Study

Abstract: BackgroundSickle cell disease (SCD) is the most common inherited disorder worldwide, with the highest burden in sub-Saharan Africa. The natural history of SCD is characterized by periods of steady state interspersed by acute episodes. The acute anemic crises may be transient and are precipitated by treatable factors like infections, nutritional deficiencies, and sequestration. Anemia is almost always present, although it occurs at different levels of severity.ObjectiveThis paper describes the protocol of a cro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The challenges associated with SCD made the World Health Organization (WHO) to declare Sickle Cell Anaemia a public health priority (Makani et al., 2013). It has been reported that poor nutrition, inadequate health care facilities and high orthodox treatment costs, are factors that further exacerbate anaemia in children with SCD (Tluway et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The challenges associated with SCD made the World Health Organization (WHO) to declare Sickle Cell Anaemia a public health priority (Makani et al., 2013). It has been reported that poor nutrition, inadequate health care facilities and high orthodox treatment costs, are factors that further exacerbate anaemia in children with SCD (Tluway et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This was a nested study investigating factors associated with severe anemia among patients admitted at Muhimbili National Hospital 10. The study population was hospitalized SCD patients with various complications between February and April 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Patient care and management for recruited study population is well described in the published protocol by Tluway et al10 Inclusion criteria were: 1) aged between 0–45 years 2) confirmed SCD-(SS/Sβ O ) by High-Performance Liquid Chromatography (HPLC), and 3) hospitalized at MNH during the study period. Patients on hydroxyurea, those who had received blood transfusion within the past four weeks and re-admission within the past four weeks were excluded from this study 10. The study was granted ethical approval by Muhimbili University of Health and Allied Science (MUHAS) Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the challenges associated with SCD, WHO has declared Sickle Cell Anaemia as a disease of municipal health concern. Studies have exposed that inadequate nutrition and health care facilities with exorbitant conventional treatment are factors that further exacerbate anaemia in children with SCD [4] SCD is associated to a mutation in a single nucleotide in the βglobin gene leading to sickle shaped haemoglobin whichpredisposes the hemoglobin with altered amino acid sequence to increased polymerization, microscopically evidenced by red blood cells (RBC) [3]. This alteration to RBC shape revisesnot only the structure but also the function of this important protein, resulting in decreased blood flow and lower oxygen supply to tissues and organs [5].…”
Section: Introductionmentioning
confidence: 99%